Capitalistic Dilemma of Merantau for Minangkabau Men Viewed through Symbolic Interaction and Relational Dialectics - Hadibroto, Joko Utomo; Agustina, Anna; Kaligis, Retor A.W.; Halim, Umar (JURNAL LENSA MUTIARA KOMUNIKASI, 2023)
The tradition of migrating in Minangkabau, West Sumatra, requires adult men to leave their hometowns in order to live independently, adapt to new environments and achieve a successful life. However, some adult men choose not to migrate for personal reasons. This research uses the concepts of Social, Cultural, and Symbolic Capital by Pierre Bourdieu, as well as the theories of Symbolic Interactionism and Relational Dialectics by Mead, Blumer, Baxter, and Montgomery to examine this capitalistic dilemma. Using these theories, the author aims to reveal the capitalistic dilemma for adult men, when each of them has reasons to choose between two options, where a certain amount of capital surrounds migrants and non-migrants, as well as the symbolic interaction and relational dialectics that occur between migrants and non-migrants. This research uses a qualitative method entitled Capitalistic Dilemma of the Merantau Tradition for Minangkabau Men Viewed Through Symbolic Interaction and Relational Dialectics. In this research, resource persons such as traditional leaders, migrants, and non-migrants were interviewed to gain in-depth insights. Although the obligation to migrate is a customary law or regulation that has been going on for generations, the results of the study prove that, migrating or not migrating is not a problem, when each individual has reasons that strengthen his choice. The decision to migrate or not is imbued with significant meaning, influenced by social, cultural, economic, and symbolic factors.